PENGARUH MEDIA PEMBELAJARAN BIGBOOK TERHADAP KEMAMPUAN MENYIMAK ANAK - Harjanty, Rokyal; Muzdalifah, Fithrii (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2021)
The purpose of this study is to find out whether there is an effect of bigbook learning media on children's listening skills. This study uses an experimental type of research using a quantitative approach to obtain complete and in-depth information about the effect of bigbook learning media on children's listening skills in group A RA Barokatussoulatiyah NW Puyung, Jonggat District, Central Lombok Regency. The population in this study amounted to 15 so that this study is said to be a population study. Furthermore, the data collected by the author uses observation, questionnaires, tests and documentation, and the type of data analysis uses the SPSS 16 stage. Based on the results of the t-test research, it shows that the bigbook learning media has a significant influence on children's listening skills, namely 95% and obtained tcount = - 23,252 and the value of sig.(2-tailed) = 0.000. Because the significant value is 0.000 < 0.005, then Ho is rejected and Hi is accepted. Thus the bigbook learning media has a positive effect on children's listening skills. From this study the teacher can find out how much influence the provision of bigbook learning media has on children's listening skills. So it is expected that teachers are more creative in choosing the media used so that students are more eager to receive lessons.